Aplikasi Pendataan dan Pelanggaran Administratif Lembaga Pemasyarakatan (LP) Kelas IIA Kota Banjarmasin Berbasis Web - Mustafa Kamaludin (Journal Information Technology Trends (JITRENDS), 2025)
The processing of visitor data, inmates, and administrative violations in Class IIA Penitentiary (LP) of Banjarmasin City has been conducted manually and semi-computerized, resulting in inefficient and inaccurate reporting. Furthermore, the absence of a security system leaves the data vulnerable to unauthorized manipulation. This research develops a web-based application to manage visitor and inmate data using the Waterfall development model. The system design uses a context diagram and Data Flow Diagram (DFD). The tools used include Sublime Text 3 and XAMPP 3.2.2 with PHP and MySQL. The resulting application is expected to help staff manage data quickly, effectively, and efficiently.